SOCIAL JUSTICE EDUCATION (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article highlights the importance of social justice education in promoting equity and social justice for historically marginalized groups. The scholars and educators recognize that social justice education can help create inclusive and effective educational systems that promote democratic participation and civic engagement. This education is intended to empower students to become advocates of change who can identify and address issues of inequality and social injustices, thereby promoting fair and equitable societies.